2017
DOI: 10.1136/bmjsem-2017-000263
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for specific lower extremity and spinal musculoskeletal injuries identified through medical screening and training load monitoring in professional football (soccer): a systematic review

Abstract: BackgroundMedical screening and load monitoring procedures are commonly used in professional football to assess factors perceived to be associated with injury.ObjectivesTo identify prognostic factors (PFs) and models for lower extremity and spinal musculoskeletal injuries in professional/elite football players from medical screening and training load monitoring processes.MethodsThe MEDLINE, AMED, EMBASE, CINAHL Plus, SPORTDiscus and PubMed electronic bibliographic databases were searched (from inception to Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(49 citation statements)
references
References 47 publications
5
44
0
Order By: Relevance
“…The dataset contained 60 candidate factors [20]. Because of the sample size considerations, before any analysis, the set of candidates was reduced based upon data quality and reliability assessment, previous evidence of prognostic value [19] and clinical reasoning [20]. This process left a final set of 10 candidate factors, represented by 12 model parameters (Table 1).…”
Section: Candidate Prognostic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dataset contained 60 candidate factors [20]. Because of the sample size considerations, before any analysis, the set of candidates was reduced based upon data quality and reliability assessment, previous evidence of prognostic value [19] and clinical reasoning [20]. This process left a final set of 10 candidate factors, represented by 12 model parameters (Table 1).…”
Section: Candidate Prognostic Factorsmentioning
confidence: 99%
“…Such models could be used to identify high-risk individuals who may require an intervention that is designed to reduce risk [17], thus assisting clinical decision making [18]. Despite the potential benefits of prognostic models for injury, we are unaware of any that have been developed using PHE data in elite football [19].…”
Section: Introductionmentioning
confidence: 99%
“…Some factors may have a strong or weak influence on the risk of injury [ 17 ] and the relative influence of each is dynamic, often changing over time [ 13 ]. To confirm factors as causal (such as those investigated during PHE), a body of high quality evidence is required [ 12 ], but this is currently lacking for injuries specifically in professional football [ 18 , 19 ] and is of variable quality in other sports [ 20 27 ]. Studies that investigate causal factors should provide detailed methodology and design, explicit definitions and measurement criteria for causal factors, confounding factors and pathological outcomes.…”
Section: Periodic Health Examination (Phe) As An Aetiological Screenimentioning
confidence: 99%
“…We prefer the PROGRESS definition for outcomes in sports medicine, as it reflects that importantly, both causal and non-causal factors can be a PF, as long as they provide information that contributes toward outcome prediction [ 14 ]. Again, this is also more reflective of PHE in professional football, as there are no clear causal links between PHE assessment and injuries [ 18 ]. One of the objectives of prognosis research is to combine several PFs within a multivariable prognostic (or prediction) model to determine the absolute risk of an injury for an individual [ 14 , 38 ].…”
Section: Phe As a Prediction/prognostic Screening Model—the Possible mentioning
confidence: 99%
“…According to Fuller et al players with cardiovascular, neurological and musculoskeletal risk factors are more likely to be injured and affected by intense exercise [10]. Hughes et al in a systematic review, concluded that medical screening tests of professional football players are defective in predicting and preventing injuries [11].…”
Section: Introductionmentioning
confidence: 99%